Sistem Pendukung Keputusan Rekomendasi Pencari Kerja menggunakan TOPSIS (Studi Kasus: PT PLN Wilayah Riau dan Kepulauan Riau) - Sukamto Sukamto; Yanti Andriyani; Chairia Oktoviani (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2021)
PT. PLN (Persero) in serving society requires quality human resources. Quality of employees in supporting the advancement of a company is very important, so that many companies are working to have quality qualified employees. One way to overcome these problems is by capturing prospective employees in accordance with the criteria desired by the company, it's just that many companies are often problematic in the process of filing and sorting because it is done manually, the result becomes not in accordance with the desired criteria of a prospective employee company. So it takes a decision support system (SPK) with the method of Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) for selection of employees who have several criteria such as the Endurance Test, Academic Test, Psych Test, Lab Test, And Interviews. Results can be concluded that the DSS employee acceptance using TOPSIS method produced a system that could provide the best applicant's recommendations in accordance with the criteria specified